Marine benthic algal flora of Ascension Island, South Atlantic. (27th August 2014) - Tsiamis, Konstantinos; Peters, Akira F.; Shewring, Dawn M.; Asensi, Aldo O.; Van West, Pieter; Küpper, Frithjof C.
Abstract : This paper provides a comprehensive checklist of the marine benthic macroalgal flora of Ascension Island (tropical South Atlantic Ocean), based on both new collections and previous literature. 82 marine macroalgae were identified from our work, including 18 green algae (Ulvophyceae), 15 brown algae (Phaeophyceae) and 49 red algae (Rhodophyta). Among our collections, 38 species and infraspecific taxa are reported for the first time from Ascension Island, including seven green, three brown and 28 red macroalgae, raising the total number of seaweeds recorded in Ascension so far to 112 taxa in species and infraspecific level. No seagrasses have been recorded at Ascension Island.